UHPC–AAC facade elements: Structural design, production technology, and mechanical behavior. Issue 4 (1st September 2018) - Miccoli, Lorenzo; Fontana, Patrick; Qvaeschning, Dirk; Kreft, Oliver; Hoppe, Johannes; Meng, Birgit
Abstract: The aim of this study was to develop a lightweight composite facade element for new buildings and for the refurbishment of existing facades. These composite elements have been developed combining an insulation layer of autoclaved aerated concrete (AAC) with an external ultrahigh‐performance concrete (UHPC) supporting layer. This solution allows avoiding the use of connectors and facilitates the production procedure. The structural behavior of the facade elements is mainly influenced by the presence of the upturning edges that are able to increase the stiffness of the element and reduce the thickness of the external layer. The insulation material has no influence on the structural behavior of the UHPC boxes. Flexural tests were carried out to investigate a potential detachment of the external layer from the upturning edge. The photogrammetric analysis used during the flexural tests essentially confirmed that the bond between the two UHPC layers cast in two steps is reliable. The quality of the bond between the external layer and the upturning edge is a key parameter to define the bearing capacity of the element.